Ecological, Behavioural and Morphometric Characteristics of the Giant Cricket (Brachytrupes membranaceus L.) in Oji River LGA, Enugu State, South East, Nigeria: A Prelude to Semi-intensive Rearing Technique (e-Proceedings of the Faculty of Agriculture International Conference, 2024)
Ecological, behavioural and morphometric characteristics of the giant cricket (Brachytrupes membranaceus L.) in two towns (Awlaw and Achi) within Oji River Local Government Area of Enugu State, South east, Nigeria was investigated as a prelude to develop useful technique for semi- intensive rearing of the insect in simulated environment. Five hundred metres land area was marked out around the locations where the index trees were found in the two localities using line transect and the sites were used as study sites and visited once every week for three months Mid-March to June ending. The result showed ten species of trees that act as indicators of the presence of the cricket in the two towns. The burrows for male Brachytrupes membranaceus cricket were significantly higher in number and more in depth compared to that of females, but there was no significant difference on the burrow width for male and female burrows. The female though more robust in appearance, did not show any significant difference (P>0.05) in the body weight when compared to males. Of all the morphometric parameters assessed, only the pronotum length and femur length showed significance differences (P
Keywords: Behavioural characteristics; Brachytrupes membranaceus; Ecological; Giant Cricket; Morphometric characteristics